2019
DOI: 10.3390/su11215874
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Agricultural Development in Iraq and the Kurdistan Region in Iraq (KRI)

Abstract: From being a smallholder-based, food-producing country covering its basic needs, Iraq and the Kurdistan Region in Iraq (KRI) have become major importers of food. The sustainability of the agricultural sector has been systematically undermined by conflict, neglect, and mismanagement, as a result of which the capacity of its farmers to feed the population declined. Even though local policymakers, the international community, and the international organisations emphasise the potential of agriculture for food prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…However, the Kurdistan Region, and especially Erbil as the capital of the region, witnessed considerable growth and development after 2004. Generally, since 1991, the KRI has been a de facto independent entity making its own regulations and policies, and according to the new constitution, which was prepared in 2005, Iraq is a federal country, with the Kurdistan Region as the only federal state within its borders [69]. Further analysis showed that the increase in built-up areas was about 25 km 2 between 1984 and 2004, which nearly equals 1.25 km 2 per year.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Kurdistan Region, and especially Erbil as the capital of the region, witnessed considerable growth and development after 2004. Generally, since 1991, the KRI has been a de facto independent entity making its own regulations and policies, and according to the new constitution, which was prepared in 2005, Iraq is a federal country, with the Kurdistan Region as the only federal state within its borders [69]. Further analysis showed that the increase in built-up areas was about 25 km 2 between 1984 and 2004, which nearly equals 1.25 km 2 per year.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the ways in which rural land was valued were changing. The devastating violence of the 1970s and 1980s going hand in hand with forced urbanization, the detrimental effects of the double embargo during the 1990s (international sanctions on Iraq and an internal Iraqi boycott on the Kurdistan Region), and the distributive measures under the Oil for Food program after 1996 have all impacted the agricultural sector profoundly (Bozarslan 2021, 120; Eklund and Lange 2018, 120; Jongerden et al 2019; Leezenberg 2005, 636; 2006, 162; Natali 2007, 1116–19; Stansfield 2003, 43; Woertz 2019). If, in the mid‐1970s, 50% of the population had still lived on agriculture (O'Shea 2004, 139), by 2012, this had been reduced to 9% (Eklund, Abdi, and Islar 2017; Eklund, Persson, and Pilesjö 2015).…”
Section: Land As Resourcementioning
confidence: 99%
“…After all, he exclaimed, “our soil is solid gold [ axê me hemî zêr e ]!” (interview, March 16, 2015). Yet, as the difficulties faced by smallholder farmers of the region attested, this “gold” was not easily turned profitable (Jongerden et al 2019; Sama 2020). Many interlocutors commented on the contrast between the perceived richness of the Kurdish soil and the actual difficulties inherent in making a living, let alone a profit, from agriculture.…”
Section: Land As Resourcementioning
confidence: 99%
“…For instance, Derunova et al [228] saw the inclusive development of the agri-food system as a driver for sustained growth in the Russian regional economy. However, Jongerden et al [229] pointed out that "Even though local policymakers, the international community, and the international organisations emphasise the potential of agriculture for food production, job creation, and income generation, they also tend to consider the current food system problematic because of an alleged low productivity", especially in developing countries. Referring to SFSCs in Quebec (Canada), Mundler and Laughrea [223] highlighted that "The most positive aspects of these systems are job creation, skills development for farmers, job satisfaction, and the adoption of sustainable agricultural practices" (p. 218).…”
Section: Economymentioning
confidence: 99%